Notes on Scaphium Kirby (Coleoptera: Staphylinidae: Scaphidiinae) with establishment of a new synonymy - Löbl, Ivan; Jałoszyński, Paweł (Zootaxa, 2024)
The diagnostic characters of Scaphium Kirby and its members are discussed and illustrated, and data on their distribution and natural history are summarized. Scaphium ferrugineum Reitter, 1880 is placed as a junior synonym of S. castanipes Kirby, 1837.